Assessment of uterine activity during IVF by quantitative ultrasound imaging: a pilot study. Issue 6 (December 2020) - Blank, Celine; Sammali, Federica; Kuijsters, Nienke; Huang, Yizhou; Rabotti, Chiara; de Sutter, Petra; Mischi, Massimo; Schoot, Benedictus
Abstract: Research question: Does uterine activity differ in patients who have undergone successful IVF treatment compared with patients who have undergone unsuccessful IVF treatment? Design: Prospective study of 16 women who underwent fresh single embryo transfer. All patients underwent transvaginal ultrasound in three phases of the IVF treatment: ovarian stimulation 1 h before embryo transfer (ET1) and 5–7 days after embryo transfer (ET5–7). Uterine motion analysis was implemented by a dedicated speckle tracking algorithm; frequency- and amplitude-related features were extracted from the derived signals to characterize the uterine activity in relation to ongoing implantation (positive HCG after 6 weeks) and ongoing pregnancy at 11 weeks. Results: Uterine activity in terms of frequency (ovarian stimulation ET1, P  = 0.04; ovarian stimulation ET5–7, P  = 0.002) and amplitude (ovarian stimulation ET1, P  = 0.0003; ovarian stimulation ET5–7, P  = 0.000008) is significantly higher in the ovarian stimulation phase compared with ET1 and ET5–7. Women with ongoing pregnancies showed significantly higher uterine contraction frequency compared with those with no ongoing pregnancies in all phases (ovarian stimulation, P  = 0.006; ET1, P  = 0.015; ET5–7, P  = 0.007). Uterine contraction amplitude was significantly lower ( P  = 0.037) in women at ET5–7 in women with ongoing pregnancies. Conclusions: This study is a first step towards assessing uterine activity during IVF objectively and non-invasively. It is an essential step to understanding the previously suggested effect of contractions on IVF failure. Uterine activity after embryo transfer characterized by high frequency and low amplitude may favour embryo implantation. Research with larger patient cohorts is needed to build on current evidence and knowledge of uterine contractions during IVF.